Atrophic Changes in Hepatocytes by Excess of Garlic Consumption - Asma Siddique, Hafiz Moeen-Ud-Din, Hafiza Sadia Ahmed, Samina Munawar,, Javed Iqbal, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Garlic (allium sativum) is proved as herbal medicine and is used as self-medication for the control of hypertension, diabetes mellitus and heart diseases. Prolonged usage and high dosage have harmful effects on liver. Aim: To evaluate the injurious effects of garlic (allium sativum) on the liver of adult albino rats. Study design: Experimental study Place and duration of study: Department of Anatomy, Shaikh Zayed Postgraduate Medical Institute, Lahore from 1st October 2013 to 31st March 2014. Methodology: Forty five wistar albino rats of both sexes weighing between 250-350 grams were selected randomly. Two different doses of 500 and 1000 mg/kg of fresh garlic extract were given to the animals by orogastric tube for thirty days. After this period the analysis of quantitative parameters including diameter of hepatic lobule, diameter of the hepatic lobules, diameters of the hepatocytes and their nucleus was then performed on the livers of the sacrificed rats. Results: In the present study, atrophic changes on the size of hepatic lobule, hepatocytes and their nucleus is noted in both experimental group B and C as compared to control group A (P<0.001). Conclusion: It is worth to note that there is a need to evaluate safe dose and to determine the optimal duration of usage of garlic in general public due to its harmful effects on liver.